Majapahit Terracotta Figurines: Social Environment and Life - Dikdik Adikara Rachman (Humaniora, 2016)
This article aimed to determine the three-dimensional visual tradition in the Majapahit kingdom. This was a manifestation of aesthetic that expressed in various forms, one of them was the figurines that represented linkage aspects in Majapahit’s community life. Terracotta was used as the main basic material in making figurines. Figurines indicated two aspects, namely the human relationship with the natural environment surrounding that translated into a mechanism for the creation, and showed the dimensions of social life in the Hindu tradition. The method used is empirical relational visual with text. In addition, the article was the result of field research conducted under the supervision of Sacred Bridge Foundation, which lasted from 2009 to 2010 in Trowulan as a heritage center site of Majapahit that spread over an area of nearly 100 km2. The research finds out that figurines as a proof of authenticity and identity of the Majapahit that understood as the embodiment of visual culture manifestation.